2008
DOI: 10.1189/jlb.0907654
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of neutrophils in the development of mechanical inflammatory hypernociception

Abstract: Neutrophil migration is responsible for tissue damage observed in inflammatory diseases. Neutrophils are also implicated in inflammatory nociception, but mechanisms of their participation have not been elucidated. In the present study, we addressed these mechanisms in the carrageenan-induced mechanical hypernociception, which was determined using a modification of the Randall-Sellito test in rats. Neutrophil accumulation into the plantar tissue was determined by the contents of myeloperoxidase activity, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
215
1
17

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(242 citation statements)
references
References 75 publications
(84 reference statements)
9
215
1
17
Order By: Relevance
“…Previous studies have shown that neutrophils may be the main effectors of inflammatory pain in different models of inflammation (20,31,37). In our study, prevention of neutrophil influx decreased joint hypernociception, demonstrating a major contribution of these cells in driving joint dysfunction after MSU crystal injection.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have shown that neutrophils may be the main effectors of inflammatory pain in different models of inflammation (20,31,37). In our study, prevention of neutrophil influx decreased joint hypernociception, demonstrating a major contribution of these cells in driving joint dysfunction after MSU crystal injection.…”
Section: Discussionsupporting
confidence: 67%
“…Inflammatory stimuli activate the release of the cytokine G-CSF that stimulates the synthesis and release of the chemokine PK2 by neutrophils, and this chemokine, in turn, stimulates macrophage chemotaxis and cytokine release by recruited macrophages. Although other leukocyte-derived chemokines are known to produce hypernociception in rats and mice (2,29,30) their pronociceptive activity and potency in activating G protein-coupled receptors is Ϸ100-500 times lower than that of PK2, and their receptors are far less abundant than PKRs in the primary sensory neurons under basal conditions (15,16,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…hypernociception ͉ inflammation ͉ prokineticin receptors I n past years, several groups have generated convincing evidence that neutrophil-associated hyperalgesia results from the neutrophil release of proinflammatory pronociceptive factors, including products of arachidonic acid metabolism (1,2) and cytokines such as IL-1␤, IL-8, IL-12, TNF-␣, and macrophage inflammatory proteins MIP-1a and MIP-1b (3,4). Belonging to the chemokine family, the recently discovered prokineticins [Bv8, MIT, prokineticin 1 (PK1), and prokineticin 2 (PK2)] (5-9) activate two G protein-linked PK receptors (PKR1 and PKR2) (10)(11)(12) localized in the brain, dorsal root ganglia (DRG) neurons, granulocytes, macrophages, and endothelial cells.…”
mentioning
confidence: 99%
“…The supernatants of isolated, cultured SGCs were collected 6 h after incubation with fractalkine (1-100 ng/mL) or medium (control) treatment. The supernatants were used to determine the levels of TNF-α and IL-1β by ELISA, as described previously (45).…”
Section: Methodsmentioning
confidence: 99%